2014
DOI: 10.1111/bjd.12542
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy of small melanomas: just miniaturized dermoscopy?

Abstract: Micromelanomas are not a rarity. However, the clinician should be aware of the fact that the majority of them lack most of the dermoscopic features presented by larger lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
61
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(67 citation statements)
references
References 41 publications
(53 reference statements)
4
61
1
1
Order By: Relevance
“…On the other hand, blue-whitish veil corresponds to epidermal acanthosis with the compact orthokeratosis typical of invasive MM. 6 Phan et al 7 reported the sensitivity of the blue-whitish veil in acral lentiginous melanoma of the palms and soles is 36%. Glomerular vessels are known to be a specific characteristic of Bowen's disease (specificity: 80%) 8 ; however, we were unable to confirm the presence of any glomerular vessels in our cases.…”
mentioning
confidence: 99%
“…On the other hand, blue-whitish veil corresponds to epidermal acanthosis with the compact orthokeratosis typical of invasive MM. 6 Phan et al 7 reported the sensitivity of the blue-whitish veil in acral lentiginous melanoma of the palms and soles is 36%. Glomerular vessels are known to be a specific characteristic of Bowen's disease (specificity: 80%) 8 ; however, we were unable to confirm the presence of any glomerular vessels in our cases.…”
mentioning
confidence: 99%
“…[1][2][3] Allowing the visualization of a series of not otherwise visible cutaneous structures, dermoscopic examination is able to significantly improve the clinical diagnosis compared with naked eye. [1][2][3][4][5][6][7][8] Several algorithms (i.e. [1][2][3][4][5][6][7][8] Several algorithms (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Several algorithms (i.e. [7][8][9][10][11][12][13][14][15][16] However, the diagnostic accuracy of these algorithms appeared to be unsatisfactory when they were applied to difficult-to-diagnose PSL (i.e. [7][8][9][10][11][12][13][14][15][16] However, the diagnostic accuracy of these algorithms appeared to be unsatisfactory when they were applied to difficult-to-diagnose PSL (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations